Perbedaan Tingkat Kemandirian Mahasiswa Ditinjau dari Pola Asuh Orang Tua Otoriter dan Demokratis - Yolanda Fenissia Kristanti; Prias Hayu Purbaning Tyas (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
The objectives of the study were to determine how high the independence of students with authoritarian and democratic parenting styles was and to determine whether or not there was a difference in the level of student independence when reviewed from authoritarian and democratic parenting patterns. This study used a quantitative approach with a comparative research design. The data collection technique used a survey with a likert scale and obtained 95 students as respondents consisting of 45 students with authoritarian parenting patterns and 50 students with democratic parenting patterns. Furthermore, it was tested using validity and reliability tests. The results of the validity test obtained 38 valid items, the reliability test used the Alpha Cronbach calculation with a result of 0.984 which was included in the very reliable category. Furthermore, a difference test was carried out using the t-test (Independent Sample T-test). The results of the study are the level of independence of students with authoritarian parenting styles was 42% in the very high category, the level of independence of students with democratic parenting styles was 40% in the very high category, and there was no difference in the level of independence between students with authoritarian and democratic parenting patterns.